Otimização do processo de adsorção de azul de metileno em zeólita A sintetizada a partir de uma nova ocorrência de caulim da região de Bom Jardim de Goiás–GO - Silva, Weber Lara Lima da (2013)
Zeolites type A were synthesized and characterized from kaolinite derived from the region of Bom Jardim de Goiás – GO, whose crystals synthesized were tested for adsorption of methylene blue in aqueous medium. The collected samples of kaolinite, and the synthesized material were characterized by X-ray diffraction, X-ray fluorescence, scanning electron microscopy, thermal analysis and infrared spectroscopy. The synthesis procedure began with obtaining the metakaolinite, by kaolinite heating at temperature of 700 °C for 2 hours. The synthesis was performed under hydrothermal conditions in solution of NaOH 4.0 mol L-1 for 3 hours at 75 °C. The characterization of the synthesized material, the XRD patterns showed a typical crystalline structure of zeolite A and through the images obtained by SEM revealed characteristic cubic crystals. The spectra showed infrared absorption bands centered at 443, 554, 657 cm-1 , characteristic of zeolite A. The average molar ratios calculated for SiO2/Al2O3 and Na2O/SiO2 were 1.226 and 0.334, respectively. Two factorial design of experiments were carried out to reduce the total number of experiments in order to achieve the best conditions for adsorption of methylene blue using as adsorbent zeolite A: It was performed a full 23 factorial design with two central points, using as factors pH, contact time (t) and the initial concentration of dye (C0). The factors pH and initial concentration of the dye and the interactions C0 ∙ pH, C0 ∙ t, pH ∙ t and C0 ∙ pH ∙ t were significant (P=0,05). These results led to an analysis of the response surface with two factors (initial concentration of dye and pH) and two central points. The best conditions for adsorption of methylene blue by zeolite A were at pH = 10 C0 = 100 mg L-1 and t = 1 h. The maximum adsorption of the dye under these conditions was 16.49 mg g-1 . The capacity of samples of zeolite A synthesized in removing the methylene blue aqueous solutions was tested by the batch method and calculated by the models of Langmuir, Freundlich, and Redlich-Peterson by the nonlinear method, the Langmuir model was the best fitted to experimental data, and adsorption calculated through this model was 40.26 mg g-1 . For the kinetic study three models were tested, pseudo-first order and pseudo-second order, and Avrami. The Avrami model showed the best fit. These results show that samples of zeolite A synthesized from the kaolin of region Bom Jardim de Goiás – GO can be considered as a good adsorbents in removing the methylene blue dye in aqueous solution.